Pengaruh Tarif Pajak, Pengetahuan Pajak, Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan (Study Kasus Wajib Pajak Kendaraan Bermotor Di Kabupaten Jepara) - Noor Salim Salim; Dian Febian Ningrum (Accounting Study Program, Faculty of Economics and Business, 2023)
This study aims to examine the effect of tax rates, tax knowledge, and service quality on motor vehicle taxpayer compliance. This type of research is quantitative research with primary data. Primary data obtained from distributing questionnaires to respondents. The population in this study are motor vehicle taxpayers who are registered at SAMSAT Jepara. Based on the Slovin formula, the sample in this study was obtained by 400 respondents. The sampling technique uses the incidental sampling method / Accidental Sampling. The results showed: (1) Tax rates have a negative and significant effect on vehicle tax compliance. (2) Tax knowledge has no effect on vehicle tax compliance. (3) Service quality has a positive effect on vehicle taxpayer compliance.